Road traffic impact on urban atmospheric aerosol loading at Oporto, Portugal - Oliveira, César (2020)
At urban areas in south Europe atmospheric aerosol levels are frequently above legislation limits as a result of road traffic and favourable climatic conditions for photochemical formation and dust suspension. Strategies for urban particulate pollution control have to take into account specific regional characteristics and need correct information concerning the sources of the aerosol. With these objectives, the ionic and elemental composition of the fine (PM2.5) and coarse (PM2.5–10) aerosol was measured at two contrasting sites in the centre of the city of Oporto, roadside (R) and urban background (UB), during two campaigns, in winter and summer. Application of Spatial Variability Factors, in association with Principal Component/Multilinear Regression/Inter-site Mass Balance Analysis, to aerosol data permitted to identify and quantify 5 main groups of sources, namely direct car emissions, industry, photochemical production, dust suspension and sea salt transport. Traffic strongly influenced PM mass and composition. Direct car emissions and road dust resuspension contributed with 44–66% to the fine aerosol and with 12 to 55% to the coarse particles mass at both sites, showing typically highest loads at roadside. In fine particles secondary origin was also quite important in aerosol loading, principally during summer, with 28–48% mass contribution, at R and UB sites respectively. Sea spray has an important contribution of 18–28% to coarse aerosol mass in the studied area, with a highest relative contribution at UB site. Application of Spatial Variability/Mass Balance Analysis permitted the estimation of traffic contribution to soil dust in both size ranges, across sites and seasons, demonstrating that as much as 80% of present dust can result from road traffic resuspension.